2011
DOI: 10.1038/bmt.2011.163
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of extramedullary relapse after haploidentical SCT for advanced AML/myelodysplastic syndrome

Abstract: Extramedullary (EM) relapse of leukemia after allo-SCT in patients with AML/myelodysplastic syndrome has been increasingly reported. The reduced effectiveness of the GVL effect in EM sites, as compared with BM, has been suggested to underlie this problem. We retrospectively analyzed the pattern of relapse after haploidentical SCT (haplo-SCT), performed as the first or second SCT. Among 38 patients who received haplo-SCT as their first SCT, the cumulative incidences of BM and EM relapse at 3 years were 40.5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
0
23
1
Order By: Relevance
“…In CML, close attention to combined morphologic and clinical characteristics allows one to accurately diagnose unusual cases with overlapping AP and BP features or those presenting as medullary BP or myeloid sarcoma at the ;17), inv (16), or t(8;21), are seen rarely in patients with BP-CML and are not associated with a favorable prognosis. TKI therapy may lead to genomic instability and acquisition of cytogenetic abnormalities in a Ph-neg clone, which underscores a need for continued cytogenetic monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CML, close attention to combined morphologic and clinical characteristics allows one to accurately diagnose unusual cases with overlapping AP and BP features or those presenting as medullary BP or myeloid sarcoma at the ;17), inv (16), or t(8;21), are seen rarely in patients with BP-CML and are not associated with a favorable prognosis. TKI therapy may lead to genomic instability and acquisition of cytogenetic abnormalities in a Ph-neg clone, which underscores a need for continued cytogenetic monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…,16 Case 327 was a 34-year-old woman diagnosed with CP-CML, treated with nilotinib, who developed lymphoblastic BP with leptomeningeal involvement. She achieved a complete remission upon induction chemotherapy, including dasatinib, and underwent allogeneic matched unrelated HST.…”
mentioning
confidence: 99%
“…Thus, systemic or combined modality therapy should be considered, particularly in patients with good performance status [10]. Donor lymphocyte infusion (DLI) has limited efficacy [14] and a second transplant often results in repeated relapse [15]. Our patient’s performance was good enough for combined modality treatment and we planned systemic chemotherapy followed by DLI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that differences in extramedullary and BM relapse were attributed to the preferential occurrence of the GVL effect after transplantation for AML with stronger GVL effects in the blood system (that is, BM and peripheral blood) over extramedullary sites. [31][32][33][34] Although the underlying mechanism has not yet been elucidated in detail, an uneven graft-versus-ATL effect may explain, at least partly, the lower frequency of leukemic relapse following allo-SCT than CHT.…”
Section: Discussionmentioning
confidence: 99%